Appearance-related distress impacts psychological symptoms in Chinese patients with cleft lip - Yichun Yang; Renjie Yang; Jiaying Wang; Zhuojun Xie; Yuan Zong; Weiyao Xia; Meijun Du; Shiming Zhang; Jiayi Yin; Jiali Chen; Bing Shi; Caixia Gong; et al. (Frontiers in Public Health)
BackgroundThis study aimed to explore the characteristics of appearance-related distress and the relationship between appearance-related distress, anxiety and depression symptoms in Chinese patients with cleft lip (CL).MethodsThe Derriford Appearance Scale 59 (DAS-59), Generalized Anxiety Disorder-7 (GAD-7), and Patient Health Questionnaire-9 (PHQ-9) were used to screen for appearance-related distress, anxiety, and depression symptoms in Chinese patients with CL, respectively.ResultsA total of 63 patients with CL, comprising 43 unilateral and 20 bilateral cases, and 64 individuals without CL in the control group were included in the study. Appearance-related distress was compared between patients with CL and non-cleft individuals. The relationship between appearance-related distress and two psychological symptoms was estimated. The DAS-59 scores in patients with CL were significantly higher than those in non-cleft individuals. The DAS-59 scores in patients with CL who had anxiety or depression symptoms were significantly higher than those without symptoms, and the DAS-59 scores were correlated with GAD-7 and PHQ-9 scores. After adjustment for demographic variables, the DAS-59 scores were also positively associated with GAD-7 and PHQ-9 scores in patients with CL.ConclusionMore significant appearance-related distress was observed in Chinese patients with CL compared to the control group, but it did not exhibit a correlation with the patients’ diagnosis (unilateral or bilateral), sex, age, or other demographic characteristics. Furthermore, appearance-related distress plays a significant role in psychological symptoms and may serve as a predictor of anxiety and depressive symptoms.